1993
DOI: 10.1152/ajpregu.1993.265.6.r1416
|View full text |Cite
|
Sign up to set email alerts
|

Biological actions of brain natriuretic peptide in thoracic inferior vena caval constriction

Abstract: Brain natriuretic peptide (BNP) shares structural and functional similarities to atrial natriuretic peptide (ANP). Although BNP and ANP interact with the same biologically active guanylate cyclase-coupled receptor, recent reports conflict with regard to the biological actions of exogenous BNP in sodium-retaining and edematous states. We studied the biological actions of BNP in normal dogs (n = 5) and sodium-avid dogs with chronic thoracic inferior vena caval constriction (TIVCC) (n = 6). In normal dogs BNP inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…In the present study, the lack of effect of ANP and BNP on PRA levels presumably reflects a balance of inhibitory actions on the juxtaglomerular apparatus (through high circulatory levels of natriuretic peptides and enhanced delivery of sodium and chloride to the macula densa) and the stimulatory effect on the afferent arteriolar baroreceptor (through the fall in renal artery perfusion pressure). Indeed, these findings are in agreement with other studies where the failure of BNP to suppress PRA was associated with a significant hypotensive response [13]. Despite the absence of PRA change during the peptide infusions, plasma aldosterone was significantly reduced by both ANP and BNP, indicating a direct inhibitory effect of the peptides on the adrenal gland.…”
Section: I63supporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, the lack of effect of ANP and BNP on PRA levels presumably reflects a balance of inhibitory actions on the juxtaglomerular apparatus (through high circulatory levels of natriuretic peptides and enhanced delivery of sodium and chloride to the macula densa) and the stimulatory effect on the afferent arteriolar baroreceptor (through the fall in renal artery perfusion pressure). Indeed, these findings are in agreement with other studies where the failure of BNP to suppress PRA was associated with a significant hypotensive response [13]. Despite the absence of PRA change during the peptide infusions, plasma aldosterone was significantly reduced by both ANP and BNP, indicating a direct inhibitory effect of the peptides on the adrenal gland.…”
Section: I63supporting
confidence: 92%
“…The fall in preload is likely to be mediated by a decrease in circulating volume and venous return (indicated by the rise in haematocrit), possibly through redistribution of plasma volume to the extravascular space [5] and through urinary loss (as evidenced by the significant diuresis in the later 2 h of the infusions). Similar haemodynamic effects have been observed by others during administration of ANP [ l l , 121 and BNP [13,141 in experimental models and in human heart failure. CO was not altered compared with a control by either ANP or BNP in the present study.…”
Section: I63supporting
confidence: 86%
See 1 more Smart Citation
“…36,37 Extensive previous studies have demonstrated the ability of human BNP to have potent cardiorenal and humoral actions in the dog. 38 Indeed, human BNP activates cGMP generation in isolated canine glomeruli. 39 While our results suggest comparable actions between M-ANP and human BNP our conclusions need to be cautious due to differences in human and canine BNP.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma and heart ANP, BNP, and CNP immunoreactivities were determined with a double-antibody radioimmunoassay as previously described. 11,25,26 Protein assay was conducted with a DC Protein assay kit (BioRad).…”
Section: Measurement Of Plasma and Heart Concentrations Of Natriuretimentioning
confidence: 99%